2019
DOI: 10.1093/jnci/djz080
|View full text |Cite
|
Sign up to set email alerts
|

Universal Tumor DNA BRCA1/2 Testing of Ovarian Cancer: Prescreening PARPi Treatment and Genetic Predisposition

Abstract: Background Women with epithelial ovarian cancer (OC) have a higher chance to benefit from poly (ADP-ribose) polymerase inhibitor (PARPi) therapy if their tumor has a somatic or hereditary BRCA1/2 pathogenic variant. Current guidelines advise BRCA1/2 genetic predisposition testing for all OC patients, though this does not detect somatic variants. We assessed the feasibility of a workflow for universal tumor DNA BRCA1/2 testing of all newly diagnosed OC patients as a prescreen for PARPi treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 24 publications
7
70
2
1
Order By: Relevance
“…In addition to the requirement of germline testing to discern whether a BRCA1/2 PV identified through tumor testing is germline or somatic in origin, continued germline testing of all cases of HGSOC remains essential as previous research has shown that inherited PVs in at least 7 genes confer a ≥ 5-fold risk of ovarian cancer [29]. Several groups have suggested that tumor results can be used to limit the number of genetics referrals for HGSOC patients by referring only those with an identified PV on tumor tissue or a suggestive clinical/family history [22,25,26]; however, a study of 7768 ovarian cancer cases found negative family history did not significantly alter ovarian cancer risk ratios, and the frequency of non-BRCA1/2 PVs increased among patients with an older age at diagnosis [29]. PVs in these non-BRCA1/2 ovarian cancer risk genes will be missed via Ontario's current targeted tumor testing, but are routinely analyzed during germline multi-gene panel testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the requirement of germline testing to discern whether a BRCA1/2 PV identified through tumor testing is germline or somatic in origin, continued germline testing of all cases of HGSOC remains essential as previous research has shown that inherited PVs in at least 7 genes confer a ≥ 5-fold risk of ovarian cancer [29]. Several groups have suggested that tumor results can be used to limit the number of genetics referrals for HGSOC patients by referring only those with an identified PV on tumor tissue or a suggestive clinical/family history [22,25,26]; however, a study of 7768 ovarian cancer cases found negative family history did not significantly alter ovarian cancer risk ratios, and the frequency of non-BRCA1/2 PVs increased among patients with an older age at diagnosis [29]. PVs in these non-BRCA1/2 ovarian cancer risk genes will be missed via Ontario's current targeted tumor testing, but are routinely analyzed during germline multi-gene panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor testing has been used by others to preserve scarce genetic counseling and testing resources by identifying the subset of HGSOC patients who warrant germline testing. For example, in a feasibility study of universal BRCA1/2 tumor testing for all newly diagnosed ovarian cancer patients in the Netherlands, Vos et al reported a 38.7% reduction in the number of required genetic tests, compared to germline-first models [25]. Yet, to provide a comprehensive assessment of hereditary cancer risk, such patient care algorithms should only be implemented when tumor testing includes analysis of all genes relevant to hereditary ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Pilot testing has found somatic GT to be feasible, effective, and acceptable to patients and providers. 20 multiple institutions is needed to validate the predictors identified here. Future work should prospectively identify factors that will further enhance our current understanding, ultimately improving quality of care for OVCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Under current guidelines, women presenting with breast or ovarian tumors are routinely tested for hereditary mutations in BRCA1/2 and this guides whether they are treated with PARP inhibitors. A recent study showed that over 40% of BRCA1/2 mutations were somatic, suggesting that the tumors should also be tested, to identify more patients that would benefit from PARP inhibitor treatment (Vos et al, 2020. ) However, growing evidence suggests that BRCA1/2 mutational status does not always accurately correlate with PARPi sensitivity (Jonsson et al, 2019) and there is a need to find more accurate predictive PARPi biomarkers.…”
Section: The Brca1 and Brca2 Genesmentioning
confidence: 99%